Qualitative and quantitative methods in health: definitions, differences and research subjects - Turato, Egberto Ribeiro (Revista de saúde pública, 2005)
The interest and accomplishments in qualitative research have been increasing in health. As a consequence, there is a greater demand for both institutional research programs and scientific journal publications. This article has the following purposes: (a) to present some definitions in qualitative methods used in Humanities and Health; (b) to compare them to the usual quantitative methods of health sciences; and, finally, (c) to illustrate the subject with the most important constructs in these methodological fields. Above all, the author's scope was to provide criteria to evaluate the pertinence of the path taken by qualitative researchers, from research plan elaboration to result interpretation.